Controller of Dynamic Reactive Power Compensation Based on FPGA - Zhao Ming; Tan Bo; Zhang Shuangfeng (Institute of Advanced Engineering and Science, 2013)
Thyristor switched capacitor (TSC) is a commonly used method of compensation of reactive power on the grid, but problems are that the compensator responses slowly and real-time tracking capability is poor. So software and hardware are developed. The fuzzy-PI controller is adopted to control TSC. And this controller is embedded in the field programmable gate array (FPGA), which can take advantage of FPGA (Field Programmable Gate Array). The detailed analysis is given. Simulation and field test show that the design improves speed, reliability and stability of the controller. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3077